BHAKTI AND MUSIC - Arya, Kajal; Naz, Sabiha (International Journal of Research -GRANTHAALAYAH, 2025)
The religion-oriented culture of India makes the Indian residents devotion-oriented, the reason for which is the relation of religion with God. Bhakti is the devotion to the beloved God with love and reverence. Bhakti is a powerful medium to connect with God. Bhakti element has been described as Amrit Swaroop and as a means to attain salvation. The most meaningful medium to express love-like devotion is music, which is called Bhakti Sangeet. The tradition of Bhakti Sangeet has been going on continuously since the Vedas. In Indian culture, the worship of the sound of Brahma in the form of Omkar is visible since the Vedic period. The Sama Bhaktis used in Samgaayan were also related to God. Gandharva was also related to divine devotion. In the course of development of history, medieval Bhakti Sangeet was reflected in the society as a golden period. The poetic verses written by Bhakti poets have become the basis of Bhakti Sangeet even in modern times. The beautiful confluence of Bhakti related poetic aspect and musical notes have made the sweet stream of Bhakti Sangeet flow among the people even today.